PERJAMUAN KUDUS MASA PENDEMI COVID-19 - Irvan Hutasoit (The New Perspective in Theology and Religious Studies, 2020)
The Lord’s Supper is a rite in the church. That rite is a remembering action of Jesus' incarnation, from His birth to His death and His resurrection. Usually, the Lord's Supper takes place and time in worship in the church. But during the Covid-19 pendemic the church was faced with the dilemma of carrying out the rite of the Lord’s Supper. So, this paper would like to explore and give an understanding of the alternatives to the implementation of the Lord's Supper when facing Covid-19 pendemi as it is today. In addition, this paper uses the meaning of the Lord's Supper as a foundation for the church to formulate its presence strategy in the world post-Covid-19.